Impact of gender, socioeconomic class and product involvement on the portrayal of women in Egyptian TV commercials - El-Mohandes, Alia (AUC Knowledge Fountain, 2020)
The study aims to analyze the relationship between the target audience gender, the socioeconomic classes, and the level of product/service involvement in the ad with the portrayal of women in Egyptian TV commercials during Ramadan 2019 from a professional perspective. Furthermore, it is essential to see if TV commercials portray women in a way that reflects the reality or challenge it in the Egyptian society. This research is both qualitative and quantitative study as it mainly depends on three methods, which are content analysis, focus groups, and In-depth interviews. The study used a census of all the ads aired on TV channels freely accessible to the Egyptian public for 30 days. From a total population of 712 ads, 100 ads met the criteria to be in the study. The results showed that when women are the target audience gender in the ad and the purchase decision maker, they are portrayed more positively than when the ad targeted men. Another finding was that the portrayal of women is more positive the higher the socioeconomic level targeted in the ad. No significant relationship was found between the level of product/service involvement and the portrayal of women in the ads. Finally, there was a significant difference in the perceived portrayal of women according to the gender of the coders who coded the ads in the content analysis process, despite them being all professionals in the marketing and advertising field.